Efl Teacher Learning In Online Community Of Practice - Putri, Fatin Fauziyyah Tiras; Damayanti, Ika Lestari (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Teachers’ professional development is essential for improving student learning outcomes and fostering overall educational quality. However, many teachers believe that TPD programs are ineffective. Teachers require ongoing programs, encouraging them to discuss ideas and give feedback, and do a collaboration. One of the programs is community of practice, which is a social learning process in which individuals with similar interest collaborate. Thus, this study aims to explore teachers’ learning in community of practice to develop their professional growth. This study adopted case study design involving a group of English teachers in Indonesia who joining an online TPD program. The data were gained through WhatsApp interaction between the teachers and the trainer, and among the teachers. The findings indicated that teachers learn in community of practice by getting proposed questions and given feedback by the trainers, getting teaching resources from the trainers and their fellow teachers, and presenting an issue related to their teaching. These aspects lead to interaction among them. Moreover, the presence of a group coordinator and administrator may help the teachers to foster teachers’ engagement towards the program.